2004
DOI: 10.1046/j.1365-2389.2004.00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing organic matter of soil aggregate coatings and biopores by Fourier transform infrared spectroscopy

Abstract: Summary In some soils, aggregate coatings and walls of biopores differ in the content of clay and organic carbon from that of the aggregate interiors or the soil matrix. The composition of the organic matter on aggregates and on the surfaces of biopores is largely unknown. We have compared the composition of organic matter between inner and outer parts of aggregates and between biopore walls and the soil matrix in a loamy arable soil and a sandy forest one. Hot‐water‐ and sodium‐pyrophosphate‐extractable organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
96
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(100 citation statements)
references
References 16 publications
4
96
0
Order By: Relevance
“…The ground samples from FTIR reflect both the surface consisting of organic compounds and the quartz core (Leue et al, 2010), while the PI samples from DRIFT represent proportionately the coating surrounding the mineral core. Previous studies from Ellerbrock and Gerke (2004) confirmed already that the KBr-technique of FTIR spectroscopy was not suitable to determine primarily the outer surface of soil particles. CONCLUSIONS 1.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The ground samples from FTIR reflect both the surface consisting of organic compounds and the quartz core (Leue et al, 2010), while the PI samples from DRIFT represent proportionately the coating surrounding the mineral core. Previous studies from Ellerbrock and Gerke (2004) confirmed already that the KBr-technique of FTIR spectroscopy was not suitable to determine primarily the outer surface of soil particles. CONCLUSIONS 1.…”
Section: Discussionmentioning
confidence: 94%
“…DRIFT ( The organic material of anaerobic digestates contains great amounts of amphiphilic components like long-chained fatty acids, which are transferred to the soil matrix after application (Täumer et al, 2005); it can flow into pore spaces or may surround mineral particles. The effect of this coating on the soil is mainly determined by the ratio of hydrophobic CH-bands to hydrophilic C=O-bands, which in term has major implications for the wetting behaviour of mineral particles (Ellerbrock and Gerke, 2004). The FTIR and DRIFT spectra of the soil-AD-mixtures indicate a change in the composition of SOM after digestate amendment: the amount of hydrophobic CH-groups is higher as compared to the unamended soil reflected by a more pronounced peak at a wavenumber of 2 920 and 2 860 cm -1 .…”
Section: Discussionmentioning
confidence: 99%
“…earthworm burrows, root channels) often create preferential flow paths and hotspots of biological activity with higher OM contents compared to the surrounding soil matrix, resulting in a spatially heterogeneous distribution of OM and CASs often in relation to the location of macropores (Bundt et al, 2001a, b;Kögel-Knabner et al, 2008;Nielsen et al, 2015). Thus, spatial variation of clay minerals and OM content in the soil profile affects the spatial distribution of CASs (Bundt et al, 2001b;Ellerbrock and Gerke, 2004;Horn, 1987). A higher density of CASs along macropores can be expected, which originates from biological activity (biopores) or is influenced by clay accumulation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, two broad bands at~1620 and~1405 cm −1 are present and originate from organic matter (Table 6) (Celi et al 1997;Cocozza et al 2003;Tivet et al 2013) and water, because the bands become weaker after heating at 180°C and disappear almost completely after treatment with hydrogen peroxide (see Szymański et al 2014). The presence of~2926 and 2855 cm −1 bands is associated with methyl and methylene groups, respectively (Ellerbrock and Gerke 2004), while the wide band at~3430 cm −1 indicates H-O-H vibrations of structurally adsorbed water molecules (Table 6) (Bain and Fraser 1994;Besson and Drits 1997;Madejová 2003). The FTIR data also indicate the lack of discernible water stagnation effects and redox effects on the different transformation pathways of clay minerals in strongly, moderately, and weakly bleached eluvial horizons as well as in eluvial horizons without bleaching.…”
Section: Ftir Spectroscopymentioning
confidence: 99%